Expressão imunohistoquímica da proteína de supressão tumoral p16ink4a como marcador de adenocarcinoma de colo uterino - Lima, Thiago Silva (2013)
Objective To evaluate the diagnostic utility of the p16ink4a protein expression as a marker for adenocarcinoma of the cervix. Methods In a cross-sectional study, p16ink4a expression was evaluated in 30 cervical biopsies from patients diagnosed with invasive adenocarcinoma from 2 reference clinics in Brazil, and compared with 18 biopsies of endocervical polyps (control cases). The performance of the tests for p16ink4a was evaluated using a conventional contingency table, and the Kappa (k) index was used to evaluate the agreement of the marker with the tissue diagnosis. Results In total, 66% of the invasive adenocarcinoma cases were positive for p16ink4a. All of the adenomatous polyps cases used as negative controls were shown to be negative for p16ink4a. The marker showed a high sensitivity and a high negative predictive value. The Kappa index was good for p16ink4a (k ¼ 0.6).Conclusion Considering the strong association between the p16ink4a marker and the cervical adenocarcinoma, its use represents an important tool for reducing incorrect. diagnoses of adenocarcinoma and thereby avoiding overtreatment.